2001
DOI: 10.1128/iai.69.1.575-578.2001
|View full text |Cite
|
Sign up to set email alerts
|

Tick Salivary Gland Extract Inhibits Killing ofBorrelia afzeliiSpirochetes by Mouse Macrophages

Abstract: Salivary gland extract (SGE) from Ixodes ricinus ticks inhibited the killing of Borrelia afzelii spirochetes by murine macrophages. SGE also reduced the production of two major defense molecules of phagocytes, superoxide and nitric oxide. It is likely that the suppression of macrophage microbicidal mechanisms contributes to the inhibitory effect of tick saliva on the killing of B. afzelii spirochetes, thus facilitating the transmission of this important pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 19 publications
2
43
0
1
Order By: Relevance
“…Similarly, Th1 immunity seems to be important for the control of Borrelia spirochete transmission (Zeidner et al 1996(Zeidner et al , 1997. Moreover, Th2-associated cytokines (IL-4, IL-10) exert a strong anti-inflammatory effect in terms of suppression of macrophage functions including production of NO, which represents an important Borrelia killing mechanism (Modolell et al 1994, Kuthejlová et al 2001. In this way, immunomodulatory effects of tick saliva facilitate pathogen transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Th1 immunity seems to be important for the control of Borrelia spirochete transmission (Zeidner et al 1996(Zeidner et al , 1997. Moreover, Th2-associated cytokines (IL-4, IL-10) exert a strong anti-inflammatory effect in terms of suppression of macrophage functions including production of NO, which represents an important Borrelia killing mechanism (Modolell et al 1994, Kuthejlová et al 2001. In this way, immunomodulatory effects of tick saliva facilitate pathogen transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased phagocytic capacity of human neutrophils and of mouse macrophages in the presence of I. ricinus or I. scapularis saliva was described (18,25). Because neutrophil infiltration is massive at the tick bite site, we hypothesized that tick saliva could facilitate bacterial propagation by decreasing NET formation.…”
Section: Effect Of I Ricinus Sge On Ros Production By Activated Humamentioning
confidence: 93%
“…The inhibitory effect of tick SGE on NK cells (Kubeš et al 1994, Kopecký and Kuthejlová 1998) and on the production of nitric oxide by macrophages (Kuthejlová et al 2001) were reported. An IL-2 binding protein was identified in the saliva of the Lyme disease vector, Ixodes scapularis (Gillespie et al 2001).…”
mentioning
confidence: 99%